A importância da negatividade hegeliana para o pensamento dialético de Herbert Marcuse: o legado da filosofia da história - Silva, Thiago Evandro Vieira da [UNESP] (2012)
This thesis aims to analyse the legacy of dialectical thought of Hegel to Critical Theory, and how it appropriates the concept of negativity as a method to overcome the antinomies inherent in capitalist society, based on the theme of Philosophy of History so trying to answer the following question: what is the importance of Hegelian negativity in Marcuse's critical theory? In methodological terms, this research sought to consider a whole contextual framework that captures the object and beyond. From the analysis of Hegel's Philosophy of History was observed near some of the concepts developed in this with those used by Critical Theory, some mediated by the historical materialism of Marx. This closeness has become more evident in the analysis of the Marcuse's Reason and Revolution text. As it was assumed that the reading of Marcuse's Hegelian system does not ignore Marx's own critique of the philosophical system of his master, demanded that this research should also considered the thought of Marx in order to better assess how the Marcuse was the appropriation of Hegelian categories.